A global guide to human resource management : managing across stakeholders - Klikauer,Thomas, 1962- (Milton Park, Abingdon, Oxon : Routledge, 2022)
'A Global Guide to Human Resource Management is a concise HRM introductory text offering a uniquely non-region-specific approach to people management in international business organisations. The book presents an alternative to standard managerial approaches, reflecting the perspectives of multiple stakeholders (workers, trade unions, states and governments, NGOs) to critically evaluate HRM in practice and, in so doing, enables students to make effective decisions in their own practice, wherever their careers take them. Its accessibility and concision make it well suited to short courses for non-HRM and non-business specialists. This text covers all major introductory topics for non-specialists, introducing the concept and purpose of HRM, through recruitment, people, skills, designing work, promoting health, rewarding success, and successful and ethical people management. This edition includes a new chapter on green HRM'--
Includes bibliographical references and index.
Keywords: Personnel management